State Asset Recovery from the Proceeds of Crime in Money Laundering in Indonesia: An Analysis of the Effectiveness and Urgency of Implementing Non-Conviction Based Asset Forfeiture (NCB) - Dilla Hariyanti; Danny Kunto Wibisono (Green Publisher Indonesia, 2026)
The return of state assets from money laundering crimes (TPPU) is a strategic component in maintaining the integrity of the financial system, national economic stability, and the effectiveness of the organized crime eradication regime. However, Indonesia's legal regime, which relies on criminal forfeiture—the confiscation of assets after a criminal verdict has obtained permanent legal force—has proven inadequate in dealing with cross-jurisdictional, multilayered, and increasingly complex TPPU. The development of financial technology, digital assets, and the use of shell companies demands a more adaptive approach. This research aims to evaluate the effectiveness of the criminal forfeiture mechanism under Law No. 8 of 2010 and to analyze the urgency of implementing non-conviction-based asset forfeiture (NCB) as an alternative. Using normative legal research methods through legislative, conceptual, and comparative approaches, this study finds that criminal forfeiture faces structural, substantive, and cultural barriers. These obstacles include the low follow-up rate on PPATK reports, the high burden of proof, and the lack of orientation among law enforcement officials toward asset recovery. Comparative studies with other countries show that NCB mechanisms are more effective in cutting off the flow of illicit funds and securing assets at an early stage. This study recommends accelerating the ratification of the Asset Forfeiture Bill, strengthening financial intelligence, and establishing an independent asset management institution as strategic steps to reinforce the asset recovery regime in Indonesia